The Archean-Paleoproterozoic structural evolution of the Caraíba Cu-Deposit, northern São Francisco Craton, Brazil: A historical review of its understanding coevally with the development of a high-risk mining project - Luiz José Homem Del-Rey Silva; André Menezes Saboia (Journal of the Geological Survey of Brazil)
The belt of basic-ultrabasic rocks within the Curaçá River Valley Province of the Bahia State, northeastern Brazil, has been known for enclosing several Cu-orebodies that helped sustain the industrial development of Brazil in the last five decades. Caraíba, Vermelhos, Surubim, Terra do Sal, Angicos, Sussuarana are the most prominent of these deposits. The Caraíba Cu-Orebody, so far the most important of all, is part of a body of Archean hypersthenites and norites that underwent poly-deformation and granulitization  in the roots of the Paleoproterozoic Itabuna-Salvador-Curaçá orogen, which records the continental collisions responsible for building the São Francisco-Congo paleocontinent in Rhyacian times, ca 2.0 Ga ago. The Caraíba Mine setup happened during the 1970 decade, together with the rush to free the country's economy from the costs of importations, exactly when the first international oil crisis (1974-1978) was suffocating the economy in many countries. Although that time coincided with the boom of geological knowledge associated with the worldwide acceptance of plate tectonics, the study of high-grade metamorphic terrains was still embryonic. In particular, the meaning of the poly-phased tectonic structures in areas recording a high degree of plasticity during deformation remained unraveled. Due to the international economic crisis, everything necessary for running the Caraíba Mine was done under pressure. Nonetheless, the coeval geological studies required for deciphering the area's structural evolution and the mineralization controls, vital for the booming mining planning and profitable exploitation of the Cu ore, had to keep the academic standards for surviving the hurry.